An Insight on the Swelling, Viscoelastic, Electrical, and Drug Release Properties of Gelatin–Carboxymethyl Chitosan Hydrogels. Issue 5 (24th March 2018) - Pandey, Preeti Madhuri; Banerjee, Indranil; Anis, Arfat; Pal, Kunal
ABSTRACT: The present study reports the in-depth analysis of the gelatin–carboxymethyl chitosan hydrogels. The composite system formed phase-separated hydrogels, which is confirmed by scanning electron microscopy. The swelling of the carboxymethyl chitosan-containing hydrogels was lower than the gelatin hydrogel. Macroscale deformation study using a static mechanical tester indicated a viscoelastic nature of the hydrogels. A decrease in the impedance of the hydrogels was observed with an increase in the carboxymethyl chitosan content. The drug release from the hydrogels was predominantly Fickian diffusion mediated and was released in its active form. The results suggested the potential use of the hydrogels as drug delivery matrices. GRAPHICAL ABSTRACT: